Free-form deformation of solid geometric models - Ng, Zhi Yu (Nanyang Technological University, 2022)
The purpose of this paper is to detail one method to re-implement Sederberg and Parry’s free-form deformation algorithm using modern programming tools. Design details and detailed implementation steps for creating a free-form deformation application are presented in this report. The advantages, disadvantages, and uses of the free-form deformation algorithm are explored to allow readers to think of further extensions and improvements that can be made to the implementation to create better tools for 3D modelling.